The Relationship between Household Food Security and Stunting Incidence in Toddlers - Alivia, Fitria; Sabri, Rika; Banowo, Agus Sri (Indonesian Journal of Global Health Research, 2024)
Stunting among children under five years old (toddler) is a fundamental challenge that must be addressed. This is due to the nutritional status of children in the first five years of life is related to cognitive development and the prevention of chronic diseases later in life. Given the high prevalence of stunting across various regions, it is necessary to conduct research to identify factors associated with stunting. Food security is one of the factors contributing to stunting based on the WHO framework. This study aimed to examine the relationship between household food security and the incidence of stunting. This study used a cohort design with retrospective approach. The retrospective method used in this approach involves first measuring stunting in children under five years old, then tracing back their household food security history to determine whether there are factors influencing the incidence of stunting. The sampling technique used was purposive sampling, and the sample size was determined using the Slovin formula, resulting in a total of 123 mothers with stunted toddlers. Chi-square analysis was used for data analysis. The chi-square test showed a p-value of 0.010. This study found a significant relationship between household food security and the incidence of stunting.